Assessment of Fruit Fly (Diptera: Tephritidae) Infestation Levels on Citrus in Abura Asebu Kwamankese District, Ghana - Bawa, S.A.; Ofori, E.S.K.; Yawson, G.; Billah, M.K.; Nuamah, K.A. (African Entomology, 2017)
Citrus spp. (Rutaceae), is a major cash crop inGhana and is cultivated in the semi-deciduous for-est zone, which covers parts of the Ashanti,Brong-Ahafo, Eastern, Western, Central and Voltaregions of the country (Anno-Nyarko 1998). Cur-rent production as at 2013 is estimated at over700 000 t annually (FAO 2013). One of the majorthreats to the citrus industry is fruit fly infestation.Fruit flies (Diptera: Tephritidae) are among themost important insect pests of fruits, especiallymangoes (Lux et al. 2003; Vayssières et al. 2008;Ekesi et al. 2009). Female fruit flies lay eggs underthe skin of the fruit, which hatch into larvae thatfeed in the decaying flesh of the crop. Infestedfruits quickly rot and become inedible or drop onthe ground, thus causing direct loss to the farmer.Besides the direct damage to the fruit, indirect lossis associated with quarantine restrictions that areimposed by fruits and vegetable importing coun-tries.
Keywords: Fruit Fly (Diptera: Tephritidae); Citrus; Abura Asebu Kwamankese District; Ghana